Psychodynamically Oriented Supportive Group Therapy With Psychotic Patients. (April 2016) - Segredou, Irini; Christodoulou, Christos; Samakouri, Maria; Antoniadou, Olga; Poulis, Evangelos; Therapou, Kyriaki; Livaditis, Miltos
This pilot study investigates the contribution of supportive psychodynamically oriented group psychotherapy to the clinical characteristics and functioning of psychotic patients. After a year of group psychotherapy using an intermediary object, the drawings of a number of psychotic patients were inspected separately so as to ascertain the improvement of psychopathological elements depicted. Two groups of 38 patients each, with similar psychopathology, clinical and demographic data were assessed before and after 1 year. One group participated in group psychotherapy, with or without an intermediary object; the other group received standard care. The study demonstrated improvement in functioning, quality of life, positive/negative symptoms, and relapses of hospitalizations for patients participating in group psychotherapy. Moreover, elements that indicate psychopathology declined in the drawings of the group in therapy with an intermediary object. Psychodynamically oriented group psychotherapy, with or without an intermediary object, could be an additional treatment option for psychotic patients.